Psychometric Properties of the Chinese Version of the Organization Big Five Scale - Meng, Yong; Yu, Boxiang; Li, Chaoping; Lan, Yuanmei (Frontiers in Psychology, 2021)
This study translates the Organization Big Five Scale (ORG-B5) into Chinese and tests its reliability and validity. In Study 1 (N = 406), the ORG-B5 was translated into Chinese, and an exploratory factor analysis established the scale’s factorial validity. In Study 2 (N = 391), confirmatory factor analyses found that the five-factor correlation model fit the data best. The results from the configural, metric, and scalar invariance models also demonstrate that the ORG-B5 is equivalent across gender, age, and work experience. The relationship between ORG-B5 and related constructs was also explored further. This study argues that the Chinese version of ORG-B5 provides researchers with a psychometrically sound and efficient tool to assess the Big Five personality traits within organizations in the Chinese context.